Moisture Sources and Atmospheric Circulation Patterns for Extreme Rainfall Event Over North China Plain From 29 July to 2 August 2023 - Hui Guo; Wanting Hu; Chen Yang; Fang Wan (Earth and Space Science)
Abstract Two years following the extreme rainfall event in Henan Province in July 2021, North China was struck by another significant rainfall episode in late July and early August 2023 (the “23.7” event). This recent event, surpassed only by the August 1963 deluge in Henan province, precipitated extensive disasters across the Beijing‐Tianjin‐Hebei region (BTH) over the North China Plain. Understanding the mechanisms underlying such extreme precipitation events, including moisture sources and atmospheric circulation patterns, in the context of synoptic‐scale systems is crucial for accurate predictions and effective disaster mitigation in the future. To achieve this, this study utilized a vertically integrated water vapor transport method and a Water Accounting model to investigate the moisture sources and pathways of the “23.7” event. A systematic analysis of circulation patterns was also conducted based on the ERA5 reanalysis. The results showed that the western North Pacific and Indian Ocean contributed 38.1% and 18.6%, respectively, to the extreme rainfall over the BTH region. Additionally, terrestrial moisture sources contributed 16.59%, playing a significant role in the event. The stable and moisture‐laden air was transported to the BTH due to the influence of binary tropical cyclones “Doksuri” and “Khanun,” as well as the western Pacific subtropical high‐pressure system. Convergence and updraft dynamics trigger convective processes modulated by vortices and topography. The findings of this study help to build a deeper understanding of the formation processes and mechanisms behind such heavy rainfall, which provides insights for model predictions of similar high‐impact low‐frequency extreme rainfall events.